Heat Flow Transport Model by Gauss-Seidel Type Iteration Methods for Gas and Solid Materials - Nurlaela Rauf; Heryanto Haeruddin; Roni Rahmat; Dahlang Tahir (Jurnal Fisika FLUX, 2021)
Technological processes for modification of materials, deposition, and prevented fumes in the pyrolysis processes are used gases materials in the medium with vacuum pressure or atmospheric air pressure. Therefore, it is essential to understand heat flow transport for designing an eﬃcient reactor or find the substrate's excellent position in the reactor or furnace for growing materials. We evaluated the energy transfer phenomena in the form of temperature distribution and heat flow for various heating sources for the gases and solid materials by Gauss-Seidel equation. The thermal conductivity coefficient (k), number of heating sources, and position of heating sources show an essential parameter for transmitting the distribution of the heat. For high k value shows efficiently for heat transfer at low temperature due to the atom's position close each other. The heat also affects to the phonon and lattice vibration like a wave which  successfully shows these phenomena in this study.